ANALISIS YURIDIS TERHADAP KERUGIAN NEGARA YANG BERASAL DARI KEUNTUNGAN REKANAN DARI PROSES PENGADAAN BARANG / JASA PEMERINTAH YANG TIDAK SAH - Zulfahmi Zulfahmi; Alvi Syahrin; Mahmud Mulyadi; Pendastaren Tarigan (USU LAW JOURNAL, 2018)
ABSTRACT Procurement of goods and services is a government procurement of goods/services that are financed with a budget of revenue and Expenditure of the State (State Budget)/Anggaran income and Expenditure area (GRANT) well that was implemented in swakelola as well as by providers of goods/ the service. In the implementation of the procurement of goods and services there are stages and procedures appointment of partner providers of goods and services is carried out through a tender open to the public and the winner must also be announced transparently to the public at large. Implementation of the designation of the partners through a tender, there is often a violation of procedure resulting in stages and the designation of the goods and service provider partners the legal disabilities because it is implemented through a tort the law. For providers of goods and services infringing in government procurement of goods and services may be subject to administrative sanction in the form of sanctions, sanctions black list registration, lawsuits are civil and/or criminal in reporting to the authorities. As for the competent authority may be subject to administrative penalties i.e. sanctions, sued for damages and/or criminal basis and reported accordingly Act No. 31 years 199 jo law No. 20 Year 2001 about criminal acts of corruption. Criminal liability against the providers of goods and services as well as the competent authority may be subject to criminal sanctions in tort law breaking the phases of procedure either in conjunction with the PA party, PPK or ULP as well as liability personally in accordance with Article 55 and 56 of the criminal code as well as Article 118 paragraph (2) Perpers No. 54 Year 2010 as it has changed four times. In tort can be categorized as corruption deeds according to experts in adverse financial and economy of the country. But other experts expressed the opinion if there was no financial loss to the State and economy and in accordance with the deed, then there can be categorized as criminal acts of corruption.   Keywords : State Losses, gains partners and Procurement of goods and services is not valid.